CLINICIAN KNOWLEDGE, COMFORT, AND PERCEIVED BARRIERS IN TREATING TRANS PATIENTS WITHIN A TERTIARY CARE PEDIATRIC CENTRE. (18th May 2018) - Butler, Kat; Johnson, Natasha
Abstract: BACKGROUND: Historically, there have been numerous barriers to trans people - including youth - in terms of their access to health care in a variety of settings. Trans-specific care for youth is sparse across the country with long wait lists to access care. Further, there is a known period of vulnerability for trans people who have decided to access transition support and have not yet received it. OBJECTIVES: This needs assessment survey was a first step to assess what training clinicians have received regarding working with trans patients, how comfortable they are working with trans patients, and what might be barriers to providing good care to trans patients. Addressing clinician perceived barriers may improve access to care. DESIGN/METHODS: A 36-question survey was distributed electronically to faculty within the departments of paediatrics and psychiatry and to paediatric residents. The anonymous survey was designed to take approximately 10 minutes. The questions covered the topics of training, comfort, and practice. Data was analysed descriptively, and will be used to inform future educational sessions. Results are reported in the following areas: Training, Comfort, Practice, Barriers and Facilitators. RESULTS: 38 clinicians completed the survey (29 faculty, 7 residents). 16% reported having received training in trans-specific care. 86% indicated interest in training in trans-related care, with the majority favouring grand rounds (74%) and online modules (71%) as learning formats. 22 respondents (58%) felt 'comfortable' or 'very comfortable' in assessing overall health of trans patients. More than 40% of respondents responded 'not applicable' to questions about prescription of puberty blockers/exogenous sex hormones, indicating that they consider this outside of their scope of practice. 82% of respondents agreed that they were aware of colleagues to whom they could refer trans patients. Two respondents (5%) indicated that they regularly provide trans-specific care. One respondent (3%) indicated having a religious and/or cultural objection to providing trans-specific health care. Most respondents reported using patients' preferred names and gender in verbal communication (89%) and when documenting (78%). 68% of respondents indicated that they would mirror language used by patients or try to use gender-neutral language when discussing anatomy. Ten participants with experience in caring for trans patients identified a variety of facilitating factors. It was noted that this is "rewarding work" and "very much needed". 76% cited a 'lack of training in trans-specific care' as the primary barrier. CONCLUSION: Information collected from the survey will assist us in creating appropriate educational sessions for the relevant departments. It is hoped that addressing clinician perceived barriers will facilitate better access to care amongst a group of patients that has historically been marginalized within health care.